[18F]FDG-6-P as a novel in vivo tool for imaging staphylococcal infections - Mills, Bethany; Awais, Ramla; Luckett, Jeni; Turton, Dave; Williams, Paul; Perkins, A.C.; Hill, P.J. (BioMed Central, 2015)
Background Management of infection is a major clinical problem. Staphylococcus aureus is a Gram-positive bacterium which colonises approximately one third of the adult human population. Staphylococcal infections can be life-threatening and are frequently complicated by multi-antibiotic resistant strains including methicillin-resistant S. aureus (MRSA). Fluorodeoxyglucose ([18F]FDG) imaging has been used to identify infection sites; however, it is unable to distinguish between sterile inflammation and bacterial load. We have modified [18F]FDG by phosphorylation, producing [18F]FDG-6-P to facilitate specific uptake and accumulation by S. aureus through hexose phosphate transporters, which are not present in mammalian cell membranes. This approach leads to the specific uptake of the radiopharmaceutical into the bacteria and not the sites of sterile inflammation.